The Nature of Licensing Centralisation under the Job Creation Law in Indonesia: Consequences of Regional Autonomy and Fiscal Capacity - Iskatrinah Iskatrinah; Hariyanto Hariyanto; Esti Ningrum; M Gholibudin Zuhaermanto (Sriwijaya Law Review, 2026)
This article discusses the constitutionality and implications of concentrating licensing authority into a single state control, following Indonesia’s Job Creation Law. Created primarily to simplify business licensing processes through the Online Single Submission Risk-Based Approach (OSS-RBA), the reform also transfers considerable authority over many aspects of licensing from regional governments to the national level. The ensuing study, therefore, questions whether this transformation is consistent with the Constitution’s promise of regional self-determination–and how it will affect regional fiscal capacity. Using a doctrinal legal approach and a quantitative comparative fiscal panel design, the article examines the 1945 Constitution (as amended), the Job Creation Law, Regional Governance Law No. 23 of 2014, relevant Constitutional Court decisions, and PAD data for all 38 Indonesian provinces for 2023–2025. These results imply a conceptual and doctrinal tension: licensing centralisation takes regional responsibility nearly beyond the regional sphere of authority. At the aggregate level, empirical results showed that provincial PAD rose between 2023 and 2025. In Papua and West Papua, meanwhile, the declines look at least as plausibly attributable to the 2022 redistricting of Papua as to the centralisation of licensing. The regional response, as noted in the Cilacap vignette, also varies across contexts depending on fiscal pressure in local areas. In the end, the piece holds that licensing centralisation is not solely an administrative enhancement but rather a constitutional issue that calls for regulatory harmonisation, meaningful local participatory development, and appropriate financial safeguards in Indonesia.